Political Communication of the Hizbut Tahrir Indonesia: A Critical Discourse Analysis - S. Sarmadan; S. Sahriadi (Universitas Sembilanbelas November Kolaka, 2017)
This study aimed to describe the political communication of Hizbut Tahrir Indonesia (HTI) so that it can be understood the ideology and political attitudes of HTI organizations in the life of nation and state.The approach used was a Critical Discourse Analysis. The analysis model was critical linguistics developed by Fowler, et al.Hence, the basic analysis refered to Halliday's explanation of the structure and function of the language into the structure of grammar. In practicing the use of grammar, the vocabulary is a choice of words (diction) to know the practice of ideology.The results showed that there were 18 choices of words (diction) in political communications in an article entitled